The â€œAll-on-Xâ€ Implant Prosthesis Opposing the Complete Overdenture on Class 2 Jaw Relation Patient - Chandra, Jefry; Atherton, Calvin; Purbasari, I Gusti Ayu Kade Ira (Indonesia Prosthodontic Association, 2021)
Nowadays, there are many treatment choices to restore the full edentulous jaw in the elderly patients, such as the implant anchoraged denture. This denture consists of fixed implant retained denture and removable implant supported overdenture. These can be considered as a viable treatment, resulting in a better esthetics, retention, and a more comfortable mastication for the patients. This article describes a 67 years old male patient complained his upper broken old dental bridge had been pulled out two months ago and required new dentures to achieve good esthetic and function. This patient had several systemic problems. From intraoral examination, the maxillary was fully edentulous with sufficient volume of alveolar ridge. Some shortened vital anterior teeth, an old metal bridge, and good posterior alveolar ridge was found in the mandible. The jaw relation was Class 2. All soft tissues were in a good condition. Because the patient refused the sinus lifting procedure, the maxilla would be restored with the â€œAll-on-Xâ€ system implant prosthesis (5 implants) with PEEK material. As the mandible would be fabricated an acrylic overdenture with some metal copings on anterior teeth and two Novaloc attachment implants in the posterior area. All the sequences of this treatment were done with mixed conventional and digital ways. An implant anchoraged denture is one of the best treatments for the edentulous patient. The good combination of examination, planning, and execution is required to achieve a positive outcome and satisfaction from the patient. The cooperation of the patient to do the maintenance well is highly required to achieve a long survival rate.